Attitudes toward and patterns of medication use among people with serious mental illness: There’s more than meets the eye - Asher, Maia; Roe, David; Hasson-Ohayon, Ilanit (Frontiers in Psychiatry, 2023)
Background and aim: There are growing concerns about the long-term effects of psychiatric medication after a major psychiatric crisis. Recent evidence shows a diverse impact of long-term use on various outcome domains, which may help explain why non-adherence is so common. In the current study we explored the subjective perceptions of factors that impact both attitudes toward and patterns of use of medication among individuals with serious mental illness (SMI). Method: Sixteen individuals with an SMI and a recognized psychiatric disability who had used psychiatric medication for at least one year were recruited for the study via mental health clinics and social media. Participants were interviewed using a semi-structured interview based on the narrative approach, focusing on attitudes toward and patterns of use of psychiatric medication. All interviews were transcribed and analyzed using thematic analysis. Results: Three discrete sequential phases emerged, each characterized by different themes referring to attitudes toward medication and patterns of use: 1) “loss of self” and a high level of medication use; 2) accumulating experiences of using/reducing/stopping medication; and 3) forming more stable attitudes toward medication and developing one’s own pattern of use. The transition between phases was dynamic in nature and represents a non-linear process. Complex interactions were generated at different phases between the related themes, which shaped attitudes toward medication and patterns of use. Conclusions and implications: The current study reveals the complex ongoing process of forming attitudes toward medication and patterns of use. Recognizing and identifying them via a joint reflective dialogue with mental health professionals can enhance alliance, shared decision-making, and person-centered recovery-oriented care.